The SWELLS survey. IV. Precision measurements of the stellar and dark matter distributions in a spiral lens galaxy - Barnabè, M; Dutton, A; Marshall, P; Auger, M; Brewer, B; Treu, T; Bolton, A; Koo, D; Koopmans, L (2012)
We construct a fully self-consistent mass model for the lens galaxy J2141 at z=0.14, and use it to improve on previous studies by modelling its gravitational lensing effect, gas rotation curve and stellar kinematics simultaneously. We adopt a very flexible axisymmetric mass model constituted by a generalized NFW dark matter halo and a stellar mass distribution obtained by deprojecting the MGE fit to the high-resolution K'-band LGSAO imaging data of the galaxy, with the (spatially constant) M/L ratio as a free parameter. We model the stellar kinematics by solving the anisotropic Jeans equations. We find that the inner logarithmic slope of the dark halo is weakly constrained (gamma = 0.82^{+0.65}_{-0.54}), and consistent with an unmodified NFW profile. We infer the galaxy to have (i) a dark matter fraction within 2.2 disk radii of 0.28^{+0.15}_{-0.10}, independent of the galaxy stellar population, implying a maximal disk for J2141; (ii) an apparently uncontracted dark matter halo, with concentration c_{-2} = 7.7_{-2.5}^{+4.2} and virial velocity v_{vir} = 242_{-39}^{+44} km/s, consistent with LCDM predictions; (iii) a slightly oblate halo (q_h = 0.75^{+0.27}_{-0.16}), consistent with predictions from baryon-affected models. Comparing the stellar mass inferred from the combined analysis (log_{10} Mstar/Msun = 11.12_{-0.09}^{+0.05}) with that inferred from SPS modelling of the galaxies colours, and accounting for a cold gas fraction of 20+/-10%, we determine a preference for a Chabrier IMF over Salpeter IMF by a Bayes factor of 5.7 (substantial evidence). We infer a value beta_{z} = 1 - sigma^2_{z}/sigma^2_{R} = 0.43_{-0.11}^{+0.08} for the orbital anisotropy parameter in the meridional plane, in agreement with most studies of local disk galaxies, and ruling out at 99% CL that the dynamics of this system can be described by a two-integral distribution function. [Abridged]